Analysis The Impact Of Massage And Physiotherapy On The Confidence Of Cycling Athletes (Journal of Pharmaceutical Negative Results, 2023)
The purpose of this study was to determine the impact of massage and physiotherapy on the confidence of cycling athletes. This research is a qualitative study using a case study method. The subjects in this study were 10 athletes who had been given massage and physiotherapy. The increase in the athlete’s confidence was measured by conducting interviews after the athlete was given massage therapy and physotherapy. The source of the data was obtained from individual in-depthinterviews directly between the interviewer and the research respondents. The interview method used is semi-structured interview. The data analysis technique in this study was carried out interactively through the process of data reduction, data display, and verification. The data is processed usingcoding, data classification, categorization, analyzing units of meaning in categories, looking for relationships between categories, making reports where the results of the analysis are suppressed in the form of draft research reports. The results of this study showed that the provision of massage and physiotherapy to the athletes can give them confidence before and after competing.Athletes will feelcomfortable when given sport massage in a prone position after training. Massaging will help to facilitate blood flow, relax muscles, and stimulate the body's work system, so that body tension will decrease, the work of the organs will return to normal, and the muscles will return to normal. The given physiotherapeutic measures successfully increase functional activity by interpretation in athletes, a decrease in self-confidence in athletes is due to the presence of pain, a decrease in the scope of motion of the joints, and a decrease in muscle strength. Therefore, with the successful reduction of the degree of pain, an increase in the scope of motion of the joints, and an increase in muscle strength, functional activity can also increase. So the given of massage and physiotherapy that researchers have done canincreasethe athlete’s confidence and make the athlete feel more primed and excited to compete. With this study, it can be seen that giving massage and physiotherapy to athletes can increase athletes' self-confidence.